The last professor has gone - Canham, Hugo ka (PINS-Psychology in Society, 2024)
What will we do now that the professor has gone? Prof Bhekizizwe Peterson cared beyond the gesture. He may be the last of that school of deep thought and care for ideas and for others. Generations of us whose lives he touched are reeling at the news of his death. We are devastated and left floundering. We fear that the project of scholarly care has lost its last soldier. Prof loved us quietly and he looked at the academy with the eyes of someone who’d seen too much.